The importance of patient’s companion towards sustainable medical tourism in Malaysia - Mohamad, Wan Normila; Omar, Azizah; Haron, Mahmod Sabri (2013)
Malaysian government considers medical tourism as one of the leading contributors towards the country’s revenue and economic growth. In sustaining and promoting the industry, it is imperative to provide continuous quality service. To do so, Malaysian private hospitals need to address the key players in this industry as well as their role in assessing the quality of medical care. While much is known generally about patient’s perspectives towards service quality, the perspectives of their families or so called “companion” towards the services is neglected. Limited research is being done to investigate on the importance of medical tourist companion in medical tourism industry. In medical tourism, accompanied companion play important roles as facilitator to enhance quality of care for patients who are receiving treatment in another country. The insight forwarded by this paper could provide some basis for future studies in this domain, particularly, on the role played by medical tourist’s companion. Doctors and nurses responsiveness, sociability, politeness, civility, capability, access, communication, accessibility of the medical doctor and the hospital staff are some constructs that can be used to measure companion’s satisfaction as well as communication, responsiveness, courtesy, cleanliness, hospital facilities and environment. Hence, companion’s satisfaction needs to be explored to improve understanding of the significant impact they have in relation to hospital service quality in Malaysian private hospitals. This study will contribute to the body of knowledge which drive the sustainability of the tourism industry in Malaysia.